Lectures on physics of high-spin states, in-beam nuclear spectroscopy - Stephens, F. S. (Frank Samuel) (Lectures on mathematics and physics. Physics, 1978)
Delivered at the Summer School in Nuclear Structure and Nuclear Reactions held at Bangalore, 1978.